Spontaneous coronary artery dissection and takotsubo syndrome: comparison of baseline clinical and angiographic characteristics and in-hospital outcomes. (25th November 2020) - Salamanca Viloria, J; Garcia-Guimaraes, M; Diez-Villanueva, P; Macaya, F; Sanz, R; Roura, G; Barahona-Alvarado, J.C; Tizon, H; Flores-Rios, X; Lezcano-Pertejo, C; Portero-Portaz, J.J; Alvarado Casas, T; et al.
Abstract: Background: Spontaneous coronary artery dissection (SCAD) and Takotsubo syndrome (TTS) constitute two relatively common non-atherosclerotic causes of acute cardiac syndrome particularly frequent in women. Methods: Herein we compared the baseline clinical and angiographic characteristics and in-hospital outcomes of 2 large prospective registries on SCAD and TTS. Results: A total of 318 SCAD and 106 TTS patients were included (88% women). Patients in the TTS group were older (Table) and presented a higher prevalence of cardiovascular risk factors. Precipitating triggers were more frequent in TTS patients (42% vs. 56%, P=0.009) but emotional stress was more common in the SCAD group (25% vs. 15%, P=0.037). SCAD patients had higher troponin and creatine-kinase levels. The left anterior descending coronary artery was the most frequently involved vessel (44%). Left ventricular dysfunction (ejection fraction 57±10 vs. 40±10%, P<0.001) was more frequently in TTS patients. Major adverse cardiovascular events (including death, myocardial infarction, ischemia-driven revascularization, development of heart failure and stroke during hospitalization) (4.7% vs. 12.3%, P<0.001) occurred more frequently in TTS patients, that also developed more frequently heart failure (<1% vs. 10%, P<0.001) and atrial fibrillation (1% vs. 11%, P<0.001). No differences were found in the rate of stroke in the 2 groups. Conclusions: TTS patients are older and present a higher prevalence of cardiovascular risk factors than SCAD patients. They also present a worse in-hospital prognosis with higher mortality. Funding Acknowledgement: Type of funding source: None